Programmed death ligand 1 (PD-L1) expression in gastric cancer: literature review - T. N. Sotnikova; N. V. Danilova; P. G. Malkov; T. V. Polushkina (Успехи молекулярной онкологии, 2023)
Gastric cancer is one of the most common oncological diseases at the present time, so research in this area is very significant and relevant. Immunological checkpoint inhibitors have previously demonstrated  their effectiveness and safety in various solid tumors, however, with regard to stomach cancer, to date, ambiguous results have been presented. Tumor cells express programmed death ligand 1 (PD-L1), which binds to its programmed death receptor 1 (PD-1). Immune defense plays a key role in the initiation and progression of the disease. Understanding the regulatory mechanism of PD-L1 in gastric cancer can lead to significant progress in immunotherapy, as well as contribute to the adequate selection of patients treated with checkpoint inhibitors. In the review, we conducted an in-depth study of PD-L1 expression and regulatory immunosuppressive mechanisms in gastric cancer and methods for assessing PD-L1 status, and also studied the results of current clinical trials in which inhibitors of immunological control points were considered in combination with and without chemotherapy for this oncopathology.